Impact of High Valence State Cation Ti/Ta Surface Doping on the Stabilization of Spinel LiNi0.5Mn1.5O4 Cathode Materials: A Systematic Density Functional Theory Investigation. Issue 12 (16th April 2018) - Chen, Yuyang; Ben, Liubin; Chen, Bin; Zhao, Wenwu; Huang, Xuejie
Abstract: Surface modification of a high‐voltage spinel LiNi0.5 Mn1.5 O4 cathode is a common method to improve its cycling performance for next generation lithium‐ion batteries, but the exact surface structural stabilization mechanism is not well‐understood. Here, detailed density function theory investigations based on the first‐principles calculations of high valence state Ti‐/Ta‐surface‐doped LiNi0.5 Mn1.5 O4 are reported. The migration of Ni/Mn ions is simulated into the surface structure of bare and Ti‐/Ta‐coated LiNi0.5 Mn1.5 O4 . The calculation results suggest that Ti/Ta doping promotes Ni/Mn migration toward the formation of the rocksalt phase. Integrated net spin suggests that the valence state of transition metal ions, especially Ni, around Ti/Ta are slightly reduced in the fully charged state, resulting in a weakened surface oxidative property toward electrolyte. Both Ti/Ta doping and the consequent formation of the rocksalt phase not only stabilizes the oxygen frame of LiNi0.5 Mn1.5 O4 by forming stronger metal‐O bonds but also suppresses the oxygen evolution during cycling. The stabilized anion frame of oxygen further mitigates the dissolution of Mn ions from the lattice into the electrolyte. These computer simulations are in good accordance with experimental observations. The surface structural stabilization mechanism of the high valence state cation Ti‐/Ta‐coated LiNi0.5 Mn1.5 O4 can certainly be expanded to improve other cathode electrode materials. Abstract : Surface modification of high‐voltage spinel LiNi0.5 Mn1.5 O4 cathode is a common method to improve its cycling performance for next generation lithium‐ion batteries. High valence state Ti/Ta surface doping remarkably reconstructs the surface from spinel to rocksalt‐like phase. Improvements of the surface rocksalt‐like phase are investigated, and the formation mechanism is discussed.